Cohen syndrome and early-onset epileptic encephalopathy in male triplets: two disease-causing mutations in VPS13B and NAPB - Alice AbdelAleem (17753799) (2023)
Cohen syndrome (CS) is a rare multisystem autosomal recessive disorder associated with mutations in VPS13B (vacuolar protein sorting homolog 13B). The NAPB-related neurodevelopmental disorder is characterized mainly by early-onset epileptic encephalopathy (EOEE) and is associated with mutations in NAPB that encodes for SNAP-beta (soluble NSF attachment protein beta). Here we describe male triplets, clinically presenting with the phenotype of subtle but distinctive facial features, intellectual disability, increased body weight, neonatal EOEE, and prominently variable abnormal behaviors of autism and sexual arousal. The EEG showed multifocal epilepsy, while the brain MRI showed no abnormalities. Diagnostic exome sequencing (ES), the applied next-generation sequencing approach, revealed the interesting finding of two novel homozygous variants in two genes: VPS13B missense variant (c.8516G > A) and NAPB splice-site loss (c.354 + 2 T > G). Sanger sequencing verified the segregation of the two recessive gene variants with the phenotype in family members. The prediction algorithms support the pathogenicity of these variants. Homozygosity mapping of ES data of this consanguineous family revealed multiple chromosomal regions of homozygosity stretches with the residing of VPS13B (chr8: 100830758G > A) and NAPB (Chr20: 23,375,774 A > C) variants within the largest homozygous blocks further supporting the disease-genes causal role. Interestingly, the functions of the two proteins; VPS13B, a transmembrane protein involved in intracellular protein transport, and SNAP-beta involved in neurotransmitters release at the neuronal synaptic complexes, have been associated with Golgi-mediated vesicular trafficking. Our ES findings provide new insights into the pathologic mechanism underlying the expansion of the neurodevelopmental spectrum in CS and further highlight the importance of Golgi and Golgi-membrane-related proteins in the development of neurodevelopmental syndromes associated with early-onset non-channelopathy epilepsy. To our knowledge, this is the first report documenting multifocal EOEE in CS patients with the association of a pathogenic NAPB variant. Other Information Published in: Neurogenetics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10048-023-00710-2